Pengaruh Mekanisme Corporate Governance Terhadap Tingkat Kepatuhan Mandatory Disclosure Konvergensi IFRS di Perbankan - Sutiyok Sutiyok; Evi Rahmawati (Universitas Muhammadiyah Yogyakarta, Indonesia, 2014)
The purpose of this study is to analyze whether the mechanism of corporate governance has the influence on the level of mandatory disclosure with the IFRS convergence. The sample used in this study is the banking industry listed at Indonesian Stock Exchange in 2011-2012. Disclosure checklist from Bapepam LK is used to identify the mandatory disclosure items. The items are adjusted to GAAP applicable in Indonesia. The results of this study indicates that the total number of meetings of the Board of Commissioners and Board of Commissioners have significant effect on the level of the compliance of the mandatory disclosure convergence with IFRS. However, the number of audit committee have no influence on the level of mandatory disclosure compliance convergence IFRS.